Analisis Profil Obat dengan ABC, VEN dan ABC-VEN untuk Optimalisasi Pengelolaan Obat Klinik Paru: Analysis Drug Profiles Thorugh ABC, VEN and ABC-VEN for Optimizing Drug Management in Pilmonary Clinics - Nova, Silvera; Suprati, Budi; Churniawan, Randhi; Prabowo, Bobby; Ratri, Dinda Monika Nusantara (Jurnal Surya Medika (JSM), 2025)
Accurate inventory control in healthcare facilities is one of the efforts to maintain service quality and financial stability, both by reducing the risk of stock shortages that hinder treatment and excess stock that triggers losses. The strategy for managing medications through data accuracy and sharp planning analysis using the ABC VEN method provides an overview of the medication profile and can be used for evaluation. This study aims to analyze the drug profile of the pulmonary clinic using the ABC VEN method. The research uses retrospective data, with samples taken from outpatient prescriptions at the pulmonary clinic of RSUD Kanjuruhan from July to December 2023, then analyzed using the ABC, VEN, and ABC-VEN methods. From 1,875 prescription samples, 85 types of drugs were obtained. The ABC analysis showed the items and percentage of drug usage in category A amounted to 4 items (73.81%), category B 8 items (16.36%), and category C 74 items (9.83%). Meanwhile, the items and percentage of investment value in category A were 2 items (74.42%), category B 6 items (16.54%), and category C 77 items (9.05%). The VEN analysis produced items and percentages: category E 82 items (99.88%), category N 3 items (0.12%), and no items were found in category V. The ABC-VEN combination includes drugs in category I AE with 2 items costing 74.42%, category II BE, CE with 80 items costing 25.46%, and drugs in category III CN with 3 items costing 0.12%. Conclusion: The ABC and VEN analysis produces different drug profiles. The ABC-VEN combination offers a more comprehensive picture by considering the usage, cost, and criticality level of drugs in the management of pharmacy in the pulmonary clinic.